2005
DOI: 10.1111/j.1600-051x.2005.00831.x
|View full text |Cite
|
Sign up to set email alerts
|

Coronally advanced flap with or without enamel matrix derivative for root coverage: a 2‐year study

Abstract: Root coverage outcomes were similar in both groups and no statistically significant differences were found at all between them. Hence, the additional use of EMD to CAF is not justified for clinical benefits of root coverage, but as an attempt of achieving periodontal regeneration rather than repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
117
0
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(143 citation statements)
references
References 19 publications
9
117
0
12
Order By: Relevance
“…They obtained slightly better outcomes with CPF‫ם‬EMD in terms of root coverage and clinical attachment level than with CPF, but the differences were not statistically significant. Other studies 6,7,20) involving more cases and longer follow-up periods also found no significant differences between CPF and CPF‫ם‬EMD. Meanwhile, several studies 3,5,18) have shown significantly better outcomes with CPF‫ם‬EMD than with CPF in terms of percentage of root coverage, keratinized gingival gain, and attachment gain, revealing substantial variability in the outcomes of long-term studies of CPF‫ם‬EMD.…”
Section: Discussionmentioning
confidence: 88%
“…They obtained slightly better outcomes with CPF‫ם‬EMD in terms of root coverage and clinical attachment level than with CPF, but the differences were not statistically significant. Other studies 6,7,20) involving more cases and longer follow-up periods also found no significant differences between CPF and CPF‫ם‬EMD. Meanwhile, several studies 3,5,18) have shown significantly better outcomes with CPF‫ם‬EMD than with CPF in terms of percentage of root coverage, keratinized gingival gain, and attachment gain, revealing substantial variability in the outcomes of long-term studies of CPF‫ם‬EMD.…”
Section: Discussionmentioning
confidence: 88%
“…While in case of the TUN procedure a split-thickness preparation is suggested to ensure a best possible blood supply to the CTG (Zuhr et al 2007), in case of CAF-treated sites a split-thickness preparation was chosen to minimize residual flap tension. Interestingly, all studies cited in the above-mentioned systematic reviews on the combined therapy of CAF with EMD basically applied this kind of a combined flap design (McGuire & Nunn 2003, Del Pizzo et al 2005, Spahr et al 2005, Castellanos et al 2006, Pilloni et al 2006, Abolfazli et al 2009), so that this aspect may at least in part serve as an explanation for the inferior results of CAF with EMD in our clinical trial. Hwang and Wang, in this connection, summarized the available evidence in a systematic review article and were able to identify a positive association between weighted flap thickness and mean and CRC (Hwang & Wang 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Calculations at the 5% significance level showed that 15 patients were sufficient to detect a difference of 1.0 AE 1.5 mm in change in GR and CAL, with a 70% statistical power while it was 80% for 20 patients (Del Pizzo et al 2005). Calculations at the 5% significance level showed that 15 patients were sufficient to detect a difference of 1.0 AE 1.5 mm in change in GR and CAL, with a 70% statistical power while it was 80% for 20 patients (Del Pizzo et al 2005).…”
Section: Power Analysismentioning
confidence: 95%